Reinterpretasi Teologi Injil Yohanes 14:6 Dalam Konteks Inklusifitas Pendidikan Agama Kristen (PAK) di Indonesia - Balo, Desy Flourensia; Brek, Yohan (PT. Giat Konseling Nusantara, 2024)
An inclusive perspective in understanding and responding to religious plurality in Indonesia is pursued through efforts to reinterpret the theology of the Gospel of John 14:6 in the context of the inclusiveness of Christian Religious Education (PAK) in Indonesia. The aim of reinterpreting this text is to offer an inclusive understanding of religious teachings in Indonesia’s pluralistic society. In carrying out this reinterpretation of theology, it is understood that the truth and the path to God must be seen from various religious perspectives, but still upholding the values of Christ. Thus, reinterpreting the theology of the Gospel of John 14:6 in the context of PAK inclusiveness in Indonesia is an important step in facing religious plurality with an inclusive attitude and expanding understanding of religious diversity in a pluralistic Indonesian society